Ownership Difference and Hospital Performance: A Theoretical Perspective - Mohiuddin, S Sultan (The International Journal of Accounting and Business Society, 1993)
This study looks at the relationship between hospital ownership and hospital performance. Efforts are made to focus on the financial rather than legal attributes of ownership by utilizing and an agency model of firm behaviour. Agency theory is a better of firm performance in hospitals than the property rights paradigm which is often applied. This is especially true where questions of ownership are often mistaken for questions of control. Importantly, the study fail to supports a property rights view of hospital ownership and performance, suggesting instead the importance of influences such as access to capital markets and the agents controlling the firm. These are key ingredients to which hospitals need to respond in today’s competitive environment.